Trending Applications of 3D Printing: A Study - Kumar, Rakesh; Kumar, Santosh (Asian Journal of Engineering and Applied Technology, 2020)
The popular name which is known by the most people and the market is 3D printing. It is an emerging manufacturing technology used to fabricate, real life parts using CAD data by adding material in layer fashion in distinct form (solid, liquid and powder). 3D printing technology is the reverse of conventional/subtractive manufacturing, owing to its design flexibility, customization, material complexity, size range, waste minimization, tool less and the ability to manufacture complicated shapes. This review paper aims to provide a comprehensive overview of distinct 3D printer applications in different sector. In addition, this review paper summarizes the merits, demerits, future and challenges, so that this review paper could become the torch bearer for the futuristic researchers working in the area of 3D printing.